Merging Grubbs second-generation catalyst with photocatalysis enables Z-selective metathesis of olefins: scope, limitations, and mechanism. Issue 41 (28th September 2022) - Chérif, Saïf Eddine; Ghosh, Avisek; Chelli, Saloua; Dixon, Isabelle M.; Kraiem, Jamil; Lakhdar, Sami
Abstract : Light is magic! The combination of Grubbs second generation catalyst, a well-known catalyst for E -selective olefin metathesis, with a photosensitizer enables efficient access to the contra-thermodynamic Z -isomers. Abstract : Olefin cross-metathesis is a cornerstone reaction in organic synthesis where stereoselectivity is typically governed by the structure of the catalyst. In this work, we show that merging Grubbs second generation catalyst, a classical E -selective catalyst, with a readily available photocatalyst, enables the exclusive formation of the contra-thermodynamic Z -isomer. The scope and limitations of this unprecedented approach are discussed based on both computational and experimental mechanistic data.